Monthly analyses of convection-related irregular flights and their linear projections for the future climate in China - Yuntao Zhou; Hongjing Gong; Penglei Fan; Na Li; Lei Gu (Environmental Research Letters, 2021)
Convective weather such as thunderstorms and rain is one of the main causes of irregular flights including delays, cancelations, turnbacks and diversions. In China, summer (April–September) flights accounted for 94% of irregular flights due to convective weather in 2016–2019. The impact of summer convective weather conditions on irregular flights is however not well understood. In this research, we find that thunderstorms, as indicated by the lifted index (LI), are greatly related to these irregular flights over Southeast China. The global climate model ensemble indicates there will be robust increases in the occurrence of convective weather environments in response to further global warming. We also find that as the LI is decreasing over time, the likelihood of thunderstorm-related irregular flights is increasing. Such an increase indicates there will be a 17% increase in irregular flights by the end of the century.